ANALISIS KONTRASTIF DALAM STUDI BAHASA - Tajudin Nur (Arabi : Journal of Arabic Studies, 2016)
Contrastive analysis is aimed to identify aspects of the differences or dissimilarities between two or more languages being contrasted. There are two kinds of approach in contrastive analysis, applied contrastive analysis and pure contrastive analysis. Both approaches contrast the first and second language, but different in the objective. Applied contrastive analysis is aimed to solve pedagogical problems, while the pure one is aimed to study language typology. Through contrastive approach there will be characteristic of every language and it is known that cultural diversity (the culture between first and second language) implicates on language forms. There are four steps to get through to contrast the components of the two languages being compared, namely (1) collecting the desired data (2) displaying a comparison in the same units of language through  language transfer, (3) identifying the different elements that exist in the language, and (4) formulating the contrasts in the rule.DOI: 10.24865/ajas.v1i2.11